Social Development Policies on Informal Sector in Solo - Wirutomo, Paulus (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
The development concept applied so far has received criticisms since it is too sectoral- and growth-oriented. This study offers a proposition that social development must – instead, get a central emphasis through developing the fundamental aspects of society, i.e.: structure, culture, and social process. By using data from qualitative research (document study, in depth interview, FGD, and observation) the writing attempts to give an illustration on how Solo Government Central Java Province conducts social development especially for street vendors. The study shows that the inclusive value- and participatory-based social development has been practiced at a certain level in Solo. The article concludes that the local government of Solo has conducted social development by relying more on structural development, through which cultural and social processes are also developed. Furthermore, there have also been dynamic, reciprocal interactions among all aspects in the social development (self-reinforcing) process in Solo. It is the basic message of this writing that, any policy study must direct its concern more towards fundamental elements of societal life, i.e. “structure, culture, and social process” .